Human serum haptoglobin is toxic to Plasmodium falciparum in vitro. - Imrie, H; Ferguson, D; Day, K (2004)
Innate immune responses are important in the control of malaria, particularly in those who have not yet mounted an effective adaptive response. Here we report that the human serum acute phase protein, haptoglobin, is toxic to Plasmodium falciparum cultured in vitro. This effect is phenotype dependent and occurs during the trophozoite phase of the asexual life cycle. We propose that the increased levels of haptoglobin seen in the acute phase response may be protective against malaria in humans.